An assessment of oral health status and treatment needs among greater Hyderabad municipal corporation workers in Hyderabad, India: A cross-sectional study - K.L. Ramitha; C.T. Anitha (Clinical Epidemiology and Global Health, 2025)
Background: Oral disease is a hidden Non-Communicable Disease (NCD) that remained a neglected concern, especially among certain occupational groups like Municipal Waste (MW) workers. Their workplace risks, high tobacco use and limited access to dental care increase vulnerability. Hence, the study aimed to assess oral health status and treatment needs among MW workers in Hyderabad, India. Methods: A cross-sectional study was conducted among MW workers in Greater Hyderabad Municipal Corporation (GHMC) at their workplace. Modified World Health Organization (WHO) Oral health questionnaire and assessment form-2013 for adults were used to record data on oral health practices and screening. Results: A total of 471MW workers participated in the study. Median age was 40 years (IQR: 35–48years); 40.1 % (189) were males and 59.9 % (282) females. Nearly 29.7 % (140) reported pain/discomfort in teeth/gums/mouth during past 12 months with 61.4 % (86) of them using self-medication. Good oral hygiene as per Oral Hygiene Index-Simplified (OHI-S) scores and dental caries was noted among 41.3 % (194) and 39.2 % (184) respectively. Ultrasonic scaling (68.8 %,324) followed by extraction of teeth (32.9 %,155) were major dental treatment needs. Educational status, nature of job and income were found to be associated with oral health intervention urgency and number of treatment needs (p < 0.05). Conclusion: This study highlights poor oral health practices and unmet dental treatment needs among MW workers. In spite of dental pain they are not seeking treatment due to their low income further hindered by work timings and wage loss. Tobacco cessation program and oral health screening alongside general health check-up at regular intervals are needed at workplace to improve their health.